PENATAAN SARANA DAN PRASARANA KAWASAN SEKOLAH TERPADU DI JALAN PURNAMA AGUNG V, KOTA PONTIANAK: PENATAAN SARANA DAN PRASARANA KAWASAN SEKOLAH TERPADU DI JALAN PURNAMA AGUNG V, KOTA PONTIANAK - Pangestu, Citra; Priyogo, Prengki; muhtadi, ahmad; Asmadi, ASMADI (Jurusan Teknik Sipil Polnep, 2023)
The arrangement of facilities and infrastructure for the Integrated School District on the road Purnama Agung V, Pontianak City is an effort to maintain the stability of nature and the function of an area that prioritizes secondary needs such as providing beauty, comfort and providing enthusiasm for learning as well as providing an attraction for residents or visitors in the area. Integrated School. The Integrated School area planning stands on an area of ​​1.94 ha consisting of 4 schools including the Early Childhood Education (PAUD) school building, SD Country 15 Pontianak South, SMP Country 22 Pontianak and SMA Country 10 Pontianak. The location of the Integrated School is located on the road Agung Purnama V, South Pontianak sub-district, Pontianak city, West Kalimantan. The planning for the arrangement of the Integrated School area with a total area of ​​1,94 Ha but that will manage with a land area of ​​0,76 Ha will be planned for green open spaces, playgrounds, reading parks, environmental roads, parking lots vehicles, drainage channels and placement of trash cans, as an effort to support the educational process and protect the environment in Indonesia, especially in the city of Pontianak, West Kalimantan.